Effect of Process Variables and Zeolite Adsorbent in Coffee Bean Drying - Soeswanto, Bambang; Edi Wahyuni, Ninik Lintang; Prihandini, Ghusrina; Pratama, Yusuf; Firmansyah, Taufik Akbar; Widyabudiningsih, Dewi (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
Green coffee beans to be stored for transportation must meet storage quality standards, especially the maximum moisture content of 12.5%, so the drying process must be carried out to achieve quality standards, but still economical. The study aims to obtain optimum operating conditions on the drying of Arabica-type coffee beans using a fluidized bed dryer assisted by zeolite adsorbents in a separated fluidized bed prior to heating, as well as calculating the energy consumption of blowers and air heater. The operating conditions were varied, namely air flow rate of 1.79 – 2.29 m/s, air temperature of 45 o C, 50 o C, and 55 o C, zeolite adsorbent mass of 150 g, 175 g, and 200 g. The coffee beans quality tests carried out were the moisture, carbohydrates, protein content, and the visual appearance of the beans. The results show that the optimum drying process of coffee beans resulting a minimum protein and carbohydrate damage are the air velocity of 2.1 m/s, air temperature of 55°C, drying time of 240 minutes, and zeolite adsorbent mass of 150 grams, with energy consumption of 5.02 KWH (equivalent to 180 MJ/T). The addition of zeolite as much as 150 grams, 175 grams, and 200 grams as adsorbent was able to reduce the relative humidity (RH) of air by 16.65%, 18.60%, and 21.17% respectively. The drying rate of coffee beans is mainly influenced by air temperature (more predominantly) than the adsorption of air humidity by zeolite.